Peran Lembaga Keuangan Syariah dalam Industri Halal sudut Pandang Maqosid Syariah - Saiful Bakhri; Kasuwi Saiban; Misbahul Munir (Program Studi Perbankan Syariah Sekolah Tinggi Agama Islam Salahuddin Pasuruan, 2022)
This paper explores the contribution of Islamic financial institutions in the halal industry from the point of view of maqashid sharia. Financial transaction activities are aimed at achieving mashlahah or economic prosperity for each person and citizen. However, the implementation of this mashlahah as the conceptual framework of sharia maqashid requires criticism that can contribute instantly to sharia business activities. The formulation of each Islamic banking and financial product is inseparable from the study of ushul fiqh and sharia maqashid. Linked to Islamic banking products, ushul fiqh with a maqashid sharia perspective shares philosophical perspectives and rational thoughts about contracts in each Islamic banking product. With the Maqashid Syariah approach, Islamic banking and financial products can grow well and can respond to rapidly changing business progress. This research uses content analysis by conducting a literature review on the theme. This paper formulates that Islamic financial institutions are driven by spirituality and ethical values ​​derived from maqashid al-syari'ah